Social and Economic Impacts of The Community With The Existence of a Cement Factory in The Tipar Kidul Village, Ajibarang Sub-district, Banyumas District - Ansori, Zakaria Al; Rusdarti, Rusdarti; Eko Handoyo, Eko (Universitas Negeri Semarang, 2018)
The development of cement factory in Indonesia every year always continuous to increase along with the development of infrastructure in Indonesia. The construction of cement industry in rural areas will have social and economic impact on the village community. The purpose of this research is to analyze the social impact of the community after cement after the establishment of a cement factory in Tipar Kidul village and analyze the economy impact of the community after the establishment of a cement factory in Tipar Kidul village, Ajibarang sub-district. Research method uses a qualitative approach. Data collection technique uses observation, interview, and documentation techniques. Data validity technique uses triangulation techniques. The results of the study showed that the establishment of a cement factory in the village of Tipar Kidul received support from the community in hopes of being able to improve the economy of the village community. The existence of a cement factory makes rural communities who are employees of a cement factory must be able to manage time to interact with their families and the community. Whereas the economic impacts of the cement factory is in term of income, employment, and living standards. Income of employees that received by cement factory, can fulfill the needs of life. The existence of a cement factory is able to increase the type of livelihood in the village, and can improve their brand’s living standards.